Reviving rationality : saving cost-benefit analysis for the sake of the environment and our health - Livermore, Michael A.; Revesz, Richard L., 1958- (New York, NY : Oxford University Press, 2020)
Under the Trump administration, inconvenient evidence has been ignored, experts have been sidelined and analysis has been used to obscure facts, rather than inform the public. The results have included haphazard and incoherent policy, social division, defeats in court, a demoralized federal workforce, and a loss of faith in government's ability to respond to the pressing problems facing American society. 'Reviving Rationality' explains how Donald Trump destabilized the decades-long bipartisan consensus that federal agencies must base their decisions on evidence, expertise and analysis.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 16, 2020).
Keywords: Political planning -- United States -- Decision making; Cost effectiveness -- Political aspects -- United States